PENGARUH GAYA KEPEMIMPINAN, LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA PERANGKAT DESA MELALUI KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING PADA KANTOR DESA KECAMATAN PANARUKAN KABUPATEN SITUBONDO - Mufida, Nurul Lailatul; Minullah, Minullah; Pramesthi, Riska Ayu (Fakultas Ekonomi dan Bisnis, 2025)
Human Resource Management (HRM) is a science or method for managing relationships and the roles of resources (labor) owned by individuals efficiently and effectively, so they can be optimally utilized to achieve the common goals of the organization, employees, and society to the fullest. The purpose of this research is to analyze and test the influence of leadership style, work environment, and work discipline on the performance of village officials through job satisfaction. The population in this study consists of all village officials in Paowan Village, Wringin Anom Village, and Kilensari Village, totaling 44 people. Data analysis and hypothesis testing in this research use the structural equation model - Partial Least Square (PLS-SEM). The results of the direct effect hypothesis test using Smart PLS 3.0 show that leadership style has a significant positive effect on job satisfaction, leadership style has a positive but not significant effect, work environment has a significant positive effect on job satisfaction, work environment has a negative but not significant effect on job satisfaction, work discipline has a positive but not significant effect on job satisfaction, and work discipline has a significant positive effect on performance. The results of the indirect effect hypothesis test show that leadership style has a positive but not significant effect on performance through job satisfaction, work environment has a significant positive effect on performance through job satisfaction, and work discipline has a positive but not significant effect on performance through job satisfaction.